How emotional labor affect hotel employees' mental health: A longitudinal study. (February 2023) - Xiong, Wei; Huang, Meijiao; Okumus, Bendegul; Leung, Xi Yu; Cai, Xiaomei; Fan, Fang
Abstract: The current study aims to examine the longitudinal effects of emotional labor on the mental health of hotel employees based on the Allostatic Load and Conservation of Resources theories. Four waves of data were collected from 534 hotel interns in an eight-month period. Latent growth modeling and lagged path analysis were used to analyze the time-series data. The study results indicated that hotel employees experienced increased anxiety and depression within the first three months of their new jobs. Surface acting increased employees' anxiety and depression. Interestingly, deep acting decreased employees' anxiety and depression in the short run but increased their anxiety and depression in the long run. Emotional exhaustion explained the double-edged effect of deep acting on mental health. The study results provide meaningful implications for hotel managers in workplace stress management and employees' mental health improvement.